2021
DOI: 10.3390/ijerph18115922
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Explanatory Variables in Possession of the Ball in High-Performance Women’s Football

Abstract: Women’s football is a phenomenon that is experiencing an unstoppable increase in recent years. The objective of this study was to analyze how ball possessions are performed in high-performance women’s football. For this, the 52 matches played by all the national teams participating in the Women’s World Cup 2015 were analyzed. A total of 3740 ball possessions were examined. Using the “move outcome” variable as a reference criterion, a statistically significant relationship was found between possessions that end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
2
10
0
2
Order By: Relevance
“…Regarding performance and offensive effectiveness, Iván‐Baragaño et al 11 analyzed the offensive phase in the FIFA Women's World Cup 2019 and proposed a predictive offensive success model based on ball possession in the attacking midfield zone with the tactical intention of progressing toward the rival goal, results which were also supported by other similar studies 12,13 ; on the contrary, the study carried out by Ibáñez et al 14 concluded that scoring the first goal of the match can mean victory in over 80% of cases in women's football if the team is well positioned in the ranking 3 …”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Regarding performance and offensive effectiveness, Iván‐Baragaño et al 11 analyzed the offensive phase in the FIFA Women's World Cup 2019 and proposed a predictive offensive success model based on ball possession in the attacking midfield zone with the tactical intention of progressing toward the rival goal, results which were also supported by other similar studies 12,13 ; on the contrary, the study carried out by Ibáñez et al 14 concluded that scoring the first goal of the match can mean victory in over 80% of cases in women's football if the team is well positioned in the ranking 3 …”
Section: Introductionmentioning
confidence: 80%
“…This instrument is well suited to the object of study and has been used in similar investigations. [10][11][12] Altmann's 26 advice on molar and molecular fit of behaviors and categories has been followed. To achieve this balance, each behavior unit conforms to the rule of the three Ds: delimitable (identifiable by themselves, presenting their own identity); denominable (the adornment of a name allows its distinction); and definable (it maintains the basis for its operation in the subsequent evaluation) (delimitable, denominable, and definable).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Este hecho puede justificarse por dos motivos. En primer lugar, algunos estudios han demostrado que la posesión de balón en campo propio no es favorable a la hora de conseguir el éxito ofensivo, tanto el fútbol femenino (Iván-Baragaño, et al, 2021;Maneiro, et al, 2021) como en fútbol masculino (Casal, et al, 2017) y, por otro lado, el hecho de mantener la posesión de balón durante menos tiempo en campo propio, puede dificultar las recuperaciones del equipo rival en zonas del terreno de juego asociadas a una mayor probabilidad de obtener éxito ofensivo (Tenga, et al, 2010;Iván-Baragaño, et al, 2021). De la misma forma, se observaron diferencias en el tiempo total de posesión.…”
Section: Discussionunclassified
“…Scanlan et al (2020) analizaron qué criterios determinaban la consecución de oportunidades de gol, encontrando que las posesiones de balón que daban comienzo mediante un robo a una interceptación, finalizaban en mayor medida en una oportunidad de gol. Por otro lado, un estudio presentado por Maneiro et al (2021) demostró que existía una asociación significativa entre el éxito ofensivo en las posesiones de balón y los criterios: i) temporalidad: se observó una mayor probabilidad de que las acciones ofensivas finalizaran con éxito en las segundas partes (p<.001); ii) intención inicial ofensiva: las posesiones que daban comienzo mediante una intención de progresar rápidamente finalizaron con éxito en mayor medida (p<.001); iii) tiempo de posesión (p<.001) y iv) número de pases (p<.001).…”
Section: Introductionunclassified